circRNA-79530 regulates Twist-mediated mitochondrial damage via sponging miR-214 affecting hypoxia/reoxygenation-induced injury in H9c2 cardiomyocytes - Ziyang Yu; Wenbo Xu; Yirong Teng; Tingting Li; Ren Guo; Ju Li; Xichen Li; Yanping Li; Yinglu Hao (European Journal of Histochemistry)
Cardiomyocyte injury related to hypoxia/reoxygenation (H/R) is pivotal in myocardial infarction. The circular RNA circRNA-79530 (circ79530) may play a regulatory role in this process, though its exact function has yet to be elucidated. This research explores the role of circRNA-79530 in H9c2 cells under H/R, with a particular focus on its interactions with miR-214 and the transcription factor Twist. It also examines their subsequent effects on mitochondrial function and oxidative stress. H9c2 cardiomyocytes were subjected to H/R to model myocardial injury. We measured circRNA-79530, miR-214, and Twist levels via RT-qPCR, with Twist protein via Western blotting. ROS levels were quantified using DCFH-DA, and cell viability and injuries were assessed through CCK-8, LDH, SOD, and MDA assays, respectively. Mitochondrial performance was assessed through various methods, including the measurement of mitochondrial membrane potential using JC-1 staining, the quantification of ATP levels, and the examination of the protein levels of mitochondrial complexes, as well as the expression of fusion proteins. Our findings indicated that downregulation of circRNA-79530 modulated miR-214 and Twist expression, influencing mitochondrial dynamics and ROS production. Knockdown of circRNA-79530 improved cell viability, reduced oxidative stress and enhanced mitochondrial function. Additionally, overexpression of miR-214 mitigated Twist expression, further supporting the effect of miR-214 in H/R conditions. circRNA-79530 could worsen oxidative stress and mitochondrial dysfunction, and regulate Twist-mediated mitochondrial damage via sponging miR-214 in H9c2 cells under H/R conditions.